Preference restrictions in computational social choice: recent progress - Elkind, E; Lackner, M; Peters, D (IJCAI/AAAI Press, 2016)
The goal of this short paper is to provide an overview of recent progress in understanding and exploiting useful properties of restricted preference domains, such as, e.g., the domains of singlepeaked, single-crossing and 1-Euclidean preferences.